Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Teams Games Tournament terhadap Motivasi Belajar PAI Siswa di SD Negeri 03 Balai Panjang - Septia Enjelita; Desti Sartini (Lembaga Yasin AlSys, 2026)
Elementary school students’ learning motivation is one of the important factors in determining the success of the learning process; however, studies that specifically examine the effectiveness of the Teams Games Tournament cooperative learning model on students’ learning motivation remain limited. This study aimed to analyze the effect of the Teams Games Tournament learning model on the learning motivation of fourth-grade students at SD Negeri 03 Balai Panjang. This study used a quantitative approach with a quasi-experimental design through a nonequivalent control group design, involving 38 students selected using saturated sampling. Data were collected through a learning motivation questionnaire that had been tested for validity and reliability, and were then analyzed using normality tests, homogeneity tests, N-Gain calculations, and independent sample t-test hypothesis testing with the assistance of SPSS 27. The results showed a difference in the increase in learning motivation between the experimental class and the control class, with the experimental class obtaining a higher posttest mean than the control class. The N-Gain score of the experimental class was in the high category at 0.91, whereas that of the control class was in the moderate category at 0.57. The hypothesis test results showed a significance value of 0.024 < 0.05, indicating a significant effect of the Teams Games Tournament learning model on students’ learning motivation. These findings contribute to the development of studies on cooperative learning and expand understanding of the effectiveness of game-based learning in increasing elementary school students’ learning motivation. The conclusion of this study confirms that the Teams Games Tournament learning model can serve as an interactive and enjoyable learning strategy, with practical implications for teachers in improving the quality of learning and opening opportunities for further research in broader contexts and variables.